Modeling a PV- diesel-battery power system: An optimal control approach - Woon, Siew Fang; Rehbock, Volker; Setiawan, Ahmad Agus (2008)
The optimal design and operation of hybrid power systems used in remote area electri-fication are difficult tasks due to a large variety of location specific factors.Several mathematical models have been proposed in literature, aiming to capture the behavior of hybrid power system and optimize its overall operating cost.In this paper, we review an existing optimal control model of a PV-diesel-battery hybrid power system.We then compare the characteristics of the model with several generic computer simulation tools.Finally, we identify the limitations of the model and propose several improvements for future development.